A mixed method study of Taiwanese mental health professional training: acquiring person-centred therapeutic relationship competence through the use of new digital technology - Liao, Faith Ruofan (2019)
Aim/Purpose: The aim of this PhD research was to improve the acquisition of the Taiwanese mental health professionals' person-centred therapeutic relationship competence by integrating the theory-designed online technology mPath in learning.